Analisis Potensi Pulau Maratua Sebagai Destinasi Pariwisata Andalan Indonesia Timur - Iya' Setyasih; Maya Wandyana Helmy (Indonesian Journal of Tourism and Leisure, 2021)
Maratua Island is a part of the National Tourism Strategic Area (KSPN), namely Derawan-Sangalaki, in Berau Regency. This study aims to analyze the potential that can be developed on Maratua Island as a tourism destination in eastern Indonesia. This research is a quantitative descriptive study. To identify the tourism potential that can be developed on Maratua Island, use a modified guide to the Analysis of the Operational Areas for Natural Tourism Objects and Attractions (ADO-ODTWA). Maratua Island has the potential as a natural tourism destination in the form of flora and fauna, coral reefs, mangrove forests, lakes, and natural panoramas that are worthy of being developed. Based on the analysis of the factors of attractiveness, accessibility, socio-economic conditions, accommodation, sapras, and water availability, the index is 84% or feasible to develop. Maratua Island is in an advantageous condition because it has its own airport and port. For this reason, the Berau Regency Government needs to promote the potential that exists in Maratua Island, a five-year work plan is made for sustainable tourism development, involves the community in tourism management and cooperates with parties so that the development of Maratua Island tourism potential can be better.